Evaluasi Kepuasan Customer Dan Kinerja Tim Manajemen Di PT. Human Resource Strengthening Sukses Istimewa - Fata Azima Alkautsar; Muhammad Arief Setiawan; Deden Akbar Izzuddin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to evaluate the performance of the management team and customer satisfaction levels at PT. Human Resource Strengthening Sukses Istimewa. The method used in this study is a survey with a descriptive research design using a quantitative approach. The population in this study consists of 60 customers who have used the services of PT. Human Resource Strengthening Sukses Istimewa, while the sampling technique used in this study is purposive sampling. The data collection instrument used in this study was a questionnaire in the form of a Google form with 27 questions, and the data was measured using a Likert scale of SS, S, N, TS, and STS, which had undergone validity and reliability tests. The results of the study based on the instruments used were declared valid and reliable with a Cronbach's Alpha of 0.989. The results of the study show that the performance of the management team of PT. Human Resource Strengthening Sukses Istimewa achieved a level of 85%, which is classified as very satisfied. In addition, the level of customer satisfaction was also at 86%, which is classified as very satisfied. However, the analysis results show that there are still several indicators that are not optimal, particularly in responding to customer complaints and service consistency. These findings indicate that improvements in the evaluation system and strengthening of internal coordination are needed to maintain customer satisfaction stability and increase the company's competitiveness. This study provides empirical contributions to the development of customer satisfaction-based service management in human resource development service companies.